Pollen Fertility and Seed Setting: Their Role in Deciding the Yield of Sorghum (Sorghum bicolor (L) Moench) under Low Temperature Regimes - Mukri, Ganapati; Biradar, B. D.; Sajjanar, G. M.; Kumar, Ramesh (International Journal of Bio-resource and Stress Management, 2016)
Experiment was conducted at Regional Agricultural Research Station, Bijapur, India, to understand the role of pollen fertility and seed setting % on the yielding potentiality of sorghum genotypes under low temperature regimes. Experiment was imposed in replicated trials on 35 sorghum genotypes, planted in RCBD design. Each set of experiment was repeated six times with an interval of 7−8 days between the experiments, so as to make peak flowering coincides with lowest possible temperature. Pollen fertility and seed setting behavior of the plant were calculated by standard formula. Correlated the pollen fertility with seed setting along with other yield attributing traits and estimated the effect of low temperature regimes on them. Results indicated that prevailing low temperature has not affected pollen fertility rather than seed set; thereby yield has much affected by low temperature. Association study indicated that pollen fertility did not has significant positive effect on yield and seed setting which plays major role in deciding the yield of the sorghum in low temperature regimes. Among the tested genotypes stay green types were more susceptible to low temperature. Varieties performed better compared to hybrids under given condition indicating their stable performance over the temperature regimes. A maintainer line, M 31-2B which was stable for pollen fertility, seed set percentage as well as yield plant-1, can be used as source for low temperature tolerance in future sorghum breeding program.